Oxidative Hydrometallurgy of Sulphide Minerals - Carrillo-Pedroza, F. R.; Soria-Aguilar, M. J.; Salinas-Rodríguez, E.; Martínez-Luevanos, A.; Pecina-Treviño, T. E.; Dávalos-Sánchez, A. (IntechOpen, 2012)
None